Effect of a Child Care Center-Based Obesity Prevention Program on Body Mass Index and Nutrition Practices Among Preschool-Aged Children. Issue 5 (September 2014) - Natale, Ruby A.; Lopez-Mitnik, Gabriela; Uhlhorn, Susan B.; Asfour, Lila; Messiah, Sarah E.
This study examined the effect of an early childhood obesity prevention program on changes in Body Mass Index (BMI) z -score and nutrition practices. Eight child care centers were randomly assigned to an intervention or attention control arm. Participants were a multiethnic sample of children aged 2 to 5 years old ( N = 307). Intervention centers received healthy menu changes and family-based education focused on increased physical activity and fresh produce intake, decreased intake of simple carbohydrate snacks, and decreased screen time. Control centers received an attention control program. Height, weight, and nutrition data were collected at baseline and at 3, 6, and 12 months. Analysis examined height, weight, and BMI z -score change by intervention condition (at baseline and at 3, 6, and 12 months). Pearson correlation analysis examined relationships among BMI z -scores and home activities and nutrition patterns in the intervention group. Child BMI z -score was significantly negatively correlated with the number of home activities completed at 6-month post intervention among intervention participants. Similarly, intervention children consumed less junk food, ate more fresh fruits and vegetables, drank less juice, and drank more 1% milk compared to children at control sites at 6 months post baseline. Ninety-seven percent of those children who were normal weight at baseline were still normal weight 12 months later. Findings support child care centers as a promising setting to implement childhood obesity prevention programs in this age group.